Metodologi Pendidikan Akhlak Dalam Perspektif Al-Qur’an (Analisis Terhadap Ayat-Ayat Al-Qur’an Ber-lafadz “Yâ yyuhâ al-Ladzîna manû”) - Syafri, Ulil Amri; Hafidhuddin, Didin; Saefudin, Didin; Nur, Ma'mun Efendi (Ta'dibuna: Jurnal Pendidikan Islam, 2014)
In the world of education methodologies play a major role in developing education. One is the methodology that explored guidance directly from the Qur’an. Reality on the ground shows that the implementation of education at every institution of Islamic education is less build philosophy and the foundation of Islamic education which scientifically refers to the Qur'an, so that akhlak education has not been implicated in both the concepts of Islamic education. As a result, the implementation of education at every educational institution does not make faith as the core of all educational activities that result in graduates do not have strong faith. This study uses literature review sourced from literature, both primary and secondary. In practice, researchers collected qualitative data that figured that described for later analysis. This research was around issues of moral education that takes the Koran as the ground, where the terms not be separated from interpretation. In this case the interpretation method used was thematic approach to interpretation, that interpretation maudû'i, supported also by the interpretation and commentary ijmali and tahlili. This method is very adequate to assist researchers in finding the concept. As for analyzing the problem, the author uses inductive thinking, namely the synthesis of thinking which departs from the facts, data, cases and knowledge of a special nature, leading to general conclusions. This mindset is used to analyze the meaning of a text thoroughly and critically. The results of this study concluded that the methodology used in the Qur'an stresses character education through research on the verses that were lafadz 'Ya ayyuhâ al-ladzîna manu' is the method of the command, method restrictions, method targhîb, and tarhîb, with all its meaning. The methodology used commands and prohibitions of the Qur'an is at once set contemplates the good and true, and these methods also determine a benchmark of evils and abuses, these distinctive according to researchers. While the methodology is a method tarhîb and targhîb and supporters of the two previous methods. Methods targhîb and tarhîb in the process is more evocative work heart and soul of man as an essential component in human moral education. Methods tarhîb or targhîb in akhlak education is an educational method that can provide a sense of serving in the role of the appearance of al-Raja 'and al-Khauf, namely fear and hope to God that which both feel is important in the effort to build a good akhlak character. While the implementation of character education methodology derived from the Qur’an are in the world of education today, especially akhlak education, could be absorbed into the educational curriculum based on understanding of curriculum development at this time. Curriculum to accommodate the methodology in akhlak education, therefore, must first define and sort out the content set forth goodness and truth then inserted to these methods. Keywords: Ayat-ayat al-Qur’an, Pendidikan akhlak, orang-orang yang beriman